Self-Perceived Viral Load and Sexual Risk Behavior Among Known HIV-Positive MSM in San Francisco, 2014. (1st July 2017) - Guigayoma, John; Chen, Yea-Hung; Snowden, Jonathan M.; Santos, Glenn-Milo; Hecht, Jennifer; Raymond, H. Fisher
Abstract : Background: Self-perceived viral suppression status among men who have sex with men (MSM) may impact HIV risk transmission behaviors. Methods: We conducted a 2014 cross-sectional survey of MSM in San Francisco and assessed differences in sexual risk behavior among known HIV-positive MSM based on viral suppression of HIV. We collected demographics, self-perceived viral load status, and sexual risk behavior and tested for viral load levels through laboratory assays. Men were categorized in a hierarchical schema of sexual risk behavior categories based on responses to questions regarding recent partners' HIV status, condom use, and sexual positioning. We used Fisher exact tests to assess for differences based on self-perceived viral load status. Results: Out of a sample of 96 known HIV-positive men, 59 men self-reported an undetectable HIV viral load and 9 men self-reported a detectable viral load consented to confirmatory laboratory testing. The sample of self-reported undetectable men had gradually larger proportions of higher-risk sexual practices, whereas the sample of detectable men was evenly distributed across sexual practices. This association was not statistically significant ( P = 0.91). Conclusion: Self-perceived viral suppression may influence sexual practices of known HIV-positive MSM, but small sample size, especially within the detectable category, hinders our ability to determine statistical significance. More research is necessary to assess how HIV-positive men account for viral load in sexual decision-making practices, and this research may inform resource allocation and clinical recommendations to maintain the health of MSM populations.